Analisis Determinan Kejadian Abortus Pada Ibu Hamil di RSUP H. Adam Malik Medan Provinsi Sumatera Utara - Repi Mariska Purba; Siti Nurmawan Sinaga; Pitri Indriani Purba; Nora Candina Lumbantoruan; Jumroh Jumroh (Jurnal Ners, 2026)
Miscarriage remains one of the major pregnancy complications contributing to maternal morbidity and potentially increasing the risk of maternal mortality if not managed appropriately. Maternal characteristics and obstetric history are considered important factors associated with miscarriage; therefore, identifying its determinants is essential to improve preventive strategies and maternal healthcare services. This study aimed to analyze the determinants of miscarriage among pregnant women at H. Adam Malik General Hospital, Medan, North Sumatra Province. A quantitative observational analytic study with a retrospective case-control design was conducted involving 120 respondents, comprising 60 cases and 60 controls. Secondary data were obtained from medical records using a structured checklist and analyzed using univariate analysis, Chi-square test, and binary logistic regression. The results showed that maternal age (p=0.020), occupation (p=0.036), gravida (p=0.013), parity (p=0.028), and previous miscarriage history (p=0.016) were significantly associated with miscarriage. Multivariate analysis identified maternal age (OR=2.842), occupation (OR=2.433), parity (OR=2.742), and previous miscarriage history (OR=3.730; p=0.012) as independent determinants, with previous miscarriage history being the strongest predictor. It was concluded that previous miscarriage history was the strongest determinant of miscarriage, highlighting the importance of strengthening maternal risk screening and obstetric history assessment through comprehensive antenatal care.